Pierre Bourdieu's Theory of Social Practice: Understanding Habitus, Capital, and the Arena in Social Life - Darmawan, Darmawan (Journal La Sociale, 2024)
Pierre Bourdieu, a prominent sociologist, developed a theory of social practice that highlights the concepts of habitus, capital, and field as a framework for understanding the dynamics of social life. Habitus refers to cognitive and behavioral dispositions formed through an individual's social experiences, while capital encompasses various forms of economic, social, cultural, and symbolic capital that determine one's position in society. The concept of field describes the social space in which individuals and groups compete to acquire and maintain capital. The interaction between these three concepts explains how social structures reproduce inequality and how individuals can change their social positions. This article aims to outline the main concepts in Bourdieu's theory and their relevance in analyzing social practices in various spheres of life, such as education, politics, and economics.